SME`s growth and open innovation : tackling SME`s family business growth challenges with open innovation - Adebayo, Funmilayo (2014)
The present economic downturn in Europe has shifted the attention of many scholars to study alternative innovation strategy which may boost innovation for SMEs and lead to growth. Many of these SMEs are family businesses and are regarded as primary driver of successful economies. Several studies on SME growth have shown the essentiality of innovation for business survival, but have not written much in the context of open innovation. The innovation process is changing from closed to open innovation processes which can enables co-innovation and collaboration in enhancement of business performance as well as job creation. However, some SMEs especially the family business still focuses on the closed innovation processes that limit high-end growth. This study argued that open innovation model can enhance Finnish economy and lead to SMEs family business`s growth. Previous studies have shown that SMES need growth and business expansion, but it based its conclusions on closed innovation systems, open innovation has not been adequately exploited in the area of growth. This study addresses the gap by focusing on SMEs and family business growth through open innovation. This study analyzes the challenges of family businesses in the perspective of SMEs and the barriers to growth through exploratory and qualitative content analysis. It showcases how open innovation can enhance SMEs business growth as well as contribute to the economic development and employment sustainability. The findings of this study have shown that open innovation can enhance SME/family`s business growth through adequate collaboration and networking with all stakeholders without internal policy biased. The major barrier of SMEs family business in adoption of open innovation concept is assumed to be protection of their intellectual property which is seen as a major asset of the firm, especially for family businesses that are generational. This study provided information to show that SMEs can benefit from Open Innovation and at the same time safeguards their intellectual properties.